2006
DOI: 10.1016/j.conb.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

The representation of numerical magnitude

Abstract: The combined efforts of many fields are advancing our understanding of how number is represented. Researchers studying numerical reasoning in adult humans, developing humans and non-human animals are using a suite of behavioral and neurobiological methods to uncover similarities and differences in how each population enumerates and compares quantities to identify the neural substrates of numerical cognition. An important picture emerging from this research is that adult humans share with non-human animals a sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
152
3
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(169 citation statements)
references
References 49 publications
(31 reference statements)
8
152
3
6
Order By: Relevance
“…It is well documented that the intraparietal sulcus (IPS) is involved in processing numerical magnitude (for reviews see Brannon, 2006;Dehaene et al, 2003). It might well be that the IPS is used for coding magnitude in general (Walsh, 2003), whether numerical or non-numerical.…”
Section: Neuroimaging Debatesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well documented that the intraparietal sulcus (IPS) is involved in processing numerical magnitude (for reviews see Brannon, 2006;Dehaene et al, 2003). It might well be that the IPS is used for coding magnitude in general (Walsh, 2003), whether numerical or non-numerical.…”
Section: Neuroimaging Debatesmentioning
confidence: 99%
“…Human processing of numbers has intrigued researchers from various disciplines such as anthropology (Urton and Brezine, 2005), linguistics (Gordon, 2004;Pica et al, 2004;Wiese, 2003), psychology (Gallistel and Gelman, 1992;Gelman and Butterworth, 2005;Moyer and Landauer, 1967), and cognitive neuroscience (Brannon, 2006;Dehaene et al, 2003;Fias et al, 2003;Nieder, 2005). Previous reviews focused on the question whether the same representation exists for different notations of numbers (i.e., the issue of abstract numerical representation; Brannon, 2006;Dehaene et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lines of research have shown that numerical processing is subserved by the bilateral intraparietal sulcus (IPS) (e.g., Arsalidou and Taylor, 2011;Butterworth, 1999;Dehaene et al, 1999;Eger et al, 2003;Kadosh et al, 2005Kadosh et al, , 2007Piazza et al, 2007;Thioux et al, 2005; see reviews by Brannon, 2006;Dehaene et al, 2003). First, patients with parietal lesions consistently show selective impairments in numerical skills (e.g., Dehaene and Cohen, 1997;Denes and Signorini, 2001;Grafman et al, 1982;Takayama et al, 1994;Warrington, 1982;Zorzi et al, 2002), whereas patients with lesions to other brain regions showed preservation of numerical skills (e.g., Butterworth et al, 2001;Cappelletti et al, 2001Cappelletti et al, , 2002Cappelletti et al, , 2005Crutch and Warrington, 2002;Diesfeldt, 1993;Jefferies et al, 2004Jefferies et al, , 2005Lemer et al, 2003;Zamarian et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It has indeed been argued that the mental representation of numbers follows WeberFechner law, so that the larger the magnitudes, the noisier the corresponding mental representations (Dehaene, 2003). In accordance with this law, an Approximate Number System (ANS) would handle large non-symbolic number magnitudes (e.g., Brannon, 2006).…”
mentioning
confidence: 99%